The morning after: what now for psychiatry research?. Issue 1 (December 2016) - Wessely, Simon; Nicholson, Krista
Abstract The UK scientific community is rightly concerned about the impact of leaving the EU on UK science. These concerns are particularly pertinent for mental health research, which is chronically underfunded in comparison to research on physical health conditions. The EU is one of the largest funders of mental health research in the world, with the UK clearly benefitting from this because of its strong track record. Any loss of funding, leadership or influence would weaken this. Likewise if we are unable to attract the best or most promising researchers from the rest of Europe, the loser will not just be research into mental health across Europe, but patients themselves. Those working on the Brexit negotiations must develop clear and coherent plans to safeguard scientific research in UK and ensure that the momentum gained in mental health policy in recent years is not lost.